Pollen counts in Hashilan Wetland sediment core, western Iran - Reza Safaierad; Lydie M Dupont; Morteza Djamali (PANGAEA, 2023)
For pollen analysis, standard analytical techniques (Faegri and Iversen, 1989) were applied for pollen extraction. Samples were treated with 10% KOH, 10% HCl, 37% HF and acetolysis. The pollen grains were extracted from the size fraction between 160 and 10 μm sieves and were mounted in silicone oil (2000 cs). Pollen extraction was carried out at the Faculty of Geography, University of Tehran and Faculty of Geoscience, University of Bremen. The pollen data reported here are count data.
In: Safaierad, Reza; Zolitschka, Bernd; Djamali, Morteza; Dupont, Lydie M; Vogt, Christoph; Matthews, Roger (2023): Pollen, grain size, loss-on-ignition, elemental and mineralogical composition, magnetic susceptibility and radiocarbon measurements in Hashilan Wetland sediment core [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.956292